2021
DOI: 10.3390/molecules26123663
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Modeling and Prebiotic Chemistry: A Review of the State-of-the-Art and Perspectives

Abstract: We review the recent progress in the modeling of plasmas or ionized gases, with compositions compatible with that of primordial atmospheres. The plasma kinetics involves elementary processes by which free electrons ultimately activate weakly reactive molecules, such as carbon dioxide or methane, thereby potentially starting prebiotic reaction chains. These processes include electron–molecule reactions and energy exchanges between molecules. They are basic processes, for example, in the famous Miller-Urey exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 100 publications
0
6
0
Order By: Relevance
“…The next question is whether it is possible to describe the primary events, and at least the onset of the chemical kinetics, in the complex mixture used by Miller. Indications in this sense have been reported in a recent work [24] where it has been shown that the electron energy spectrum can be determined using state-ofthe-art methods for a realistic mixture matching that of the Miller-Urey original experiment and for variants describing less reducing primordial atmospheres. A model including many of the sophistications described above has been developed for lightning in the primordial atmosphere [25].…”
Section: Towards a Faithful Description Of The Primary Events In The ...mentioning
confidence: 92%
“…The next question is whether it is possible to describe the primary events, and at least the onset of the chemical kinetics, in the complex mixture used by Miller. Indications in this sense have been reported in a recent work [24] where it has been shown that the electron energy spectrum can be determined using state-ofthe-art methods for a realistic mixture matching that of the Miller-Urey original experiment and for variants describing less reducing primordial atmospheres. A model including many of the sophistications described above has been developed for lightning in the primordial atmosphere [25].…”
Section: Towards a Faithful Description Of The Primary Events In The ...mentioning
confidence: 92%
“…Furthermore, the method has been recently coupled with detailed plasma chemistry models in Refs. [71][72][73][74].…”
Section: Discretization Of the Electron Velocity Distribution Functionmentioning
confidence: 99%
“…code is an MC code for the simulation of electrons under swarm conditions. Recent work with ELIOS includes benchmarking against solutions of two-term and multi-term BE solvers and simulations in atomic and molecular gases using variance reduction techniques [31,32,43].…”
Section: Elios the Electron And Ion Simulation (Elios)mentioning
confidence: 99%